E-service Quality Measurement From Customers' Point of View - Vencovský, Filip; Voříšek, Jiří, 1950-; Pour, Jan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
This thesis focuses on the quality diagnosis of services delivered using IT artefacts over the internet that are also known as e-services, IT services or self-services. The thesis reflects new challenges and new possibilities that digital economy brings. This work examines the relationship between consumers’ feedback and service quality. The research issue is split in two particular branches. One branch is related to feedback sentiment and the other to feedback emotionality. The first particular issue refers to classification from unstructured feedback, the second to service quality implication. In order to solve the issues, the thesis presents the literature review of current service quality research and the review of opinion mining methods that can help with a large customer-generated online service feedback. This work contains the first literature review of papers that use opinion mining technique to service quality diagnosis. In contrast to the reviewed work, the thesis conceptualises service quality theory and synthesises it with opinion mining taxonomy. The case study from e-banking service is used for demonstration of opinion mining methods for service quality diagnosis. The emotions are examined in the second case study. Finally, the qualitative study on the level of a review is conducted.
Vedoucí práce: Jiří Voříšek
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor disert. práce]; disertace; dissertations